Modelling the biological control of tomato root-knot nematode by predatory mites in the presence of an alternative prey - do Prado, T. J. [UNESP]; Rossini, L. J. [UNESP]; Luquet, M.; Soares, P. L.M. [UNESP]; Castilho, R. C.; Tricault, Y. (International Society for Horticultural Science (ISHS), 2023)
Root-knot nematodes (RKN, Meloidogyne spp.) are major pests of the tomato crop. Several predatory mites (PM) species have proven to be good candidates for the development of biological control strategies against these plant-parasitic nematodes. Recent studies have shown that soil supplementation with non-parasitic, free-living nematodes (FLN), as alternative prey for PM, could improve the biological control of RKN. To investigate the effects of direct (predation) and indirect (apparent competition) interactions between pest and non-pest nematodes sharing a common predator on pest control, we developed a stage-structured population dynamic model. This model was parametrized using experimental data and information from the literature for the case of a tomato pot and the species Meloidogyne incognita (RKN), Rabditella axei (FLN) and Protogamasellopsis zaheri (PM). We simulated five scenarios over a 110-days growing season by varying PM release rates (no PM, single release, weekly release) and the presence-absence of FLN. Our results confirmed the potential of PM as biocontrol agents and highlighted the effect of the timing of FLN inoculation. The scenario combining a single early release of PM with a delayed inoculation of FLN two weeks later provided satisfactory control, at the same level as the weekly mite releases. We also detected apparent competition between the two nematode species when FLN were inoculated early on. Our model can guide the design of RKN management strategies. The next steps in development should include interactions with tomato plants (gall formation and indirect effects on nematodes and mites) as well as soil effects on the three species.
Keywords: apparent competition; free-living nematodes; Meloidogyne; Mesostigmata; population dynamics; supplementary food